Effect of homogeneous acidic catalyst on mechanical strength of trishydrazone hydrogels: Characterization and optimization studies - Nor Hakimin Abdullah; Wan Azelee Wan Abu Bakar; Rafaqat Hussain; Mohd Bakri Bakar; Jan H.van Esch (Saudi Chemical Society, 2016)
Characterization utilizing X-ray photoelectron spectroscopy (XPS) revealed the presence of all the expected elements found in trishydrazone hydrogels (3). Morphological study on confocal laser scanning microscopy (CLSM) and atomic force microscopy (AFM) revealed the branching and bundling of fibers that led hydrogels network as well as the presence of cross-linked nanofibrillar network structure. A three-factor three-level Box Behnken design was implemented to study the concurrent effects of three main variables (concentration of precursor; 10–20 mM, pH; 3–7, and concentration of buffer; 50–150 mM) on mechanical strength of hydrogels. Analysis of variance (ANOVA) was conducted to investigate the potential interactive and quadratic effects between these variables and revealed that interaction between the pH value and the concentration of buffer (X2X3) showed a significant effect on the response since the significance of the design model (p-value) was set at <0.05. Experimental results showed that acid catalyst at pH 5 had a significant effect on mechanical properties of hydrogels compared to uncatalyzed condition at pH 7 where the mechanical strength at pH 5 is almost 10 times higher than pH 7. The processing conditions that contributed to an optimum hydrogels setting were found at concentration of precursor = 20 mM, pH = 5 and concentration of buffer = 100 mM.